Issues and Countermeasures in the Canadian Stock Market: A Theoretical Analysis - Qi Yunfei (SHS Web of Conferences)
The Canadian stock market plays a fundamental role in the global economy, providing a means of capital movement and investment. But, in reality, there are a few main roadblocks that are inhibiting market effectiveness and performance. This paper discusses three problems that confront the Canadian stock market – liquidity inefficiency, sectorial focus, and regulatory insecurity. Inactivity, especially in small and mid-cap stocks slowed down trades and added to the transaction charges. The excessive focus of the market on natural assets and financial services leaves it vulnerable to sectoral shocks and lacks diversification. In addition, regulatory fragmentation retards and imposes costs. In response to these issues, the essay suggests enhancing liquidity through foreign investment and increased retail involvement, sectoral diversification through the creation of new sectors such as technology and streamlining the regulatory landscape by consolidating into a more integrated framework. These measures are made to boost the strength and global appeal of the Canadian stock market, to maintain long-term economic stability and prosperity.